1998
DOI: 10.1002/(sici)1097-0282(199803)45:3<239::aid-bip6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced conformational changes and phase behavior of aqueous poly-L-lysine solutions

Abstract: Poly‐L‐lysine exists as an α‐helix at high pH and a random coil at neutral pH. When the α‐helix is heated above 27°C, the macromolecule undergoes a conformational transition to a β‐sheet. In this study, the stability of the secondary structure of poly‐L‐lysine in solutions subjected to shear flow, at temperatures below the α‐helix to β‐sheet transition temperature, were examined using Raman spectroscopy and CD. Solutions initially in the α‐helical state showed time‐dependent increases in viscosity with shearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In a first step, upon increasing the temperature, intramolecular hydrogen bonds stabilizing the helix configuration break and PLL reversibly adopts this random structure. Further, increasing thermal motion facilitates hydrophobic interactions between lysine side groups, stimulating β-sheet formation, which is irreversible 32 47 . The higher intensity of hydrophobic interactions at elevated temperatures is the basis for the increased propensity for β-sheet formation under these conditions 47 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first step, upon increasing the temperature, intramolecular hydrogen bonds stabilizing the helix configuration break and PLL reversibly adopts this random structure. Further, increasing thermal motion facilitates hydrophobic interactions between lysine side groups, stimulating β-sheet formation, which is irreversible 32 47 . The higher intensity of hydrophobic interactions at elevated temperatures is the basis for the increased propensity for β-sheet formation under these conditions 47 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Further, increasing thermal motion facilitates hydrophobic interactions between lysine side groups, stimulating β-sheet formation, which is irreversible 32 47 . The higher intensity of hydrophobic interactions at elevated temperatures is the basis for the increased propensity for β-sheet formation under these conditions 47 48 . The positive enthalpy necessary for breaking the hydrogen bonds and association of the lysyl residues forming the β-structure is provided by the heating process 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The observed conformational change and subsequent aggregation of the sheared samples was thought to involve flow-enhanced hydrophobic interactions between individual poly-L-lysine molecules in solution. 87 Further studies, via real-time circular birefringence measurements, showed a reversible, shear-induced, helix-to-coil transition of poly-L-lysine in simple shear flow. 24 The conformational transition was observed at a critical strain rate of 300 s 21 , and the change was attributed to a shear-induced breakage of intramolecular hydrogen bonds in a-helical poly-L-lysine.…”
Section: Molecular Models and Theoretical Aspectsmentioning
confidence: 98%
“…87 A combination of Raman spectroscopy (collected in situ) and circular dichroism were employed for data acquisition in a Couette flow cell at 150 s 21 . In addition, a flow induced-gelation and an increase in the b-sheet content of the samples was observed in solution concentrations [0.3 g/dL.…”
Section: Molecular Models and Theoretical Aspectsmentioning
confidence: 99%
“…However, a number of experimental and theoretical reports in the literature are yet to reconcile differences between measurement and prediction. For example, flow-induced unfolding of insulin, 21 lysozyme, 15,22 von Willebrand factor, [23][24][25][26][27][28][29][30][31] lamda bacteriophage DNA, 32,33 and several molecular weights of poly-L-lysine 14,34,35 have been reported for a variety of well characterised flow geometries. Shear induced conformational changes in protein solutions have been measured at shear rates <10 3 s À1 (shear strain z10 5 ) while the deformation of DNA coils occurred at even lower shear rates, <4 s À1 (shear strain z10).…”
Section: Introductionmentioning
confidence: 99%